Pengaruh Pengalaman, Pengetahuan, Audit Tenure dan Peer Review Terhadap Kualitas Audit (Studi Empiris Pada KAP Di Wilayah Kota Medan) - Nikita Situmeang; Novita Grasella Vefri Yanti Tampubolon; Renawati Sianturi; Noviani Santaria Simaremare; Aremi Evanta (JURNAL MUTIARA AKUNTANSI, 2019)
This study aims to determine the effect of experience, knowledge, audit tenure and peer review on audit quality (empirical studies on KAP in the city area of Medan). This research is a survey research with a quantitative population approach in this study covering KAP in Medan. The sample was taken by samling technique of 65 auditors. Data collection techniques using questionnaires and research models are multiple linear regression. The results of the study with hypothesis testing showed that experience, knowledge and peer review simultaneously had a significant effect on audit quality. Testing the hypothesis also shows that experience, knowledge and peer review individually have a significant effect on audit quality, but audit tenure individually has no significant effect on audit quality. The hypothesis determination coefficient value adjusts R2 by 43.7% which indicates that audit quality can be explained by variations in the variables of experience, knowledge, audit tenure and other peer reviews not submitted in this study. Keywords : Experience, Knowledge, Audit Tenure, Peer Review and Audit Quality